Pathogenicity of entomopathogenic fungi Lecanicillium lecanii and Beauveria bassiana against Pseudococcus jackbeardsleyi (Pseudococcidae) infecting rambutan - Ginting, Sempurna; Djamilah; Pamekas, Tunjung; Bustaman, Hendri; Priyatiningsih; Sipriyadi; Wibowo, Risky Hadi (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Pseudococcus jackbeardsleyi is an important pest that attacks rambutan fruit (Nephelium lappaceum L.). The P. jackbeardsleyi can cause severe damage in rambutan because it is able to survive in postharvest commodities. Therefore, is a need to control this pest to avoid losses. The species of P. jackbeardsleyi can be controlled by either chemical means using insecticides or biological means using entomopathogenic fungi. Between the two control measures, the use of entomopathogenic fungi is an environmental friendly control measure and causes no harm to human health. The purpose of this study was to examine the pathogenicity of entomopathogenic fungi Lecanicillium lecanii and Beauveria bassiana against P. jackbeardsleyi (Pseudococcidae) on rambutan. The application method was by spraying P. jackbeardsleyi with fungi conidia suspension. The data obtained was analysed using the Statistical Analysis System (SAS) program. The results showed that L. lecanii + soap was the most effective cause of mortality for P. jackbeardsleyi, then L. lecanii, and B. bassiana + soap, while the lowest was B. bassiana. Based on this study, the use of entomopathogenic fungi is effective against P. jackbeardsleyi in rambutan.